Flexible graphene/silver nanoparticles/aluminum film paper for high-performance electromagnetic interference shielding. (January 2022) - Li, Xiang; Qu, Yifei; Wang, Xiu; Bian, Huiyang; Wu, Weibing; Dai, Hongqi
Graphical abstract: Highlights: Graphene/silver nanoparticles coating exhibited timely transfer of electrons and heat due to the 3D electric conductive network. The aluminum film played the dual functions of electromagnetic interference shielding and heat transfer. The material showed excellent electrical conductivity and electromagnetic interference shielding effectiveness of 4431 S/m and 92.29 dB, respectively. The material exhibited outstanding mechanical properties with tensile strength of 32 MPa and elongation at break of 6.65%. Abstract: Rubber and plastic are widely acted as substrates in flexible electromagnetic shielding (EMS) materials. However, these materials have several drawbacks in practical applications, such as potential environmental concerns and difficulties in degrading. In this work, a biodegradability paper-based material composed of electromagnetic wave loss layer (graphene/ silver nanoparticles (AgNPs) coating) and reflective layer (aluminum film layer) was successfully fabricated. The electromagnetic wave loss layer constructed three-dimensional (3D) electric conductive network to facilitate the timely transfer of electrons and heat energy obtained from electromagnetic waves. Meanwhile, the reflective layer received electrons and heat from the electric conductive network and make a small quantity of transmission wave back to the wave loss layer. The resulting material exhibited an ultrahigh electromagnetic interference shielding effectiveness (EMI SE) of 92.29 dB within 8–13 GHz, electrical conductivity of 4431 S/m, mechanical properties with a tensile strength of 32 MPa and elongation at break of 6.65%. Compared to the traditional EMS materials, the composite material integrated with excellent EMI SE, heat transfer performance, and weatherability, which has potential applications in microelectronics, high integrated circuits, and flexible electronic fields.